Building in Assyria A Philological Perspective - Tudeau, Johanna (Schriften zur Vorderasiatischen Archäologie, 2019)
Johanna Tudeau offers with this book a sketch of the practice and ideology of building in Assyria based on textual evidence. The study focuses on the Assyrian royal inscriptions and state archives, two of the most comprehensive textual corpora available on the topic. The temporal and spatial framework is necessarily broad, from the rise to the fall of Assyria, from one end of the empire to the other. This stands in contrast with a targeted terminological approach: architectural keywords structure the chapters and these follow the stages of the building process. The findings come together in a chapter devoted to the modern significance of ancient realities, where grounds for the investigation and interpretation of space are proposed to serve philologists and archaeologists alike, hopefully facilitating the exchange between disciplines.